EXPERT SYSTEM TO DIAGNOSE ERYTHEMA MULTIFORME USING THE CERTAINTY METHOD WEB-BASED FACTOR - Fahrizal Alwafi Chandra Susi Syafriana Barus; Heri Santoso; Ilka Zufria (Sean Institute, 2022)
In some cases, this disease can cause complications, such as blood poisoning, septic shock, skin infections (cellulite), permanent skin damage, permanenteye damage, and inflammation of body organs such as the liver and lungs. So that patients find it difficult to get information about Erythema Multiforme and how to handle it. The system that has been designed before has not implemented the client server feature so as to facilitate centralized database processing. Always back up data in order to avoid possible loss of important data caused by damage to the hardware. Then an expert system web will be designed to diagnose diseases in Erythema Multiforme using the Certainty Factor method. This expert web system reasoning uses a chain that is traversed from a chain that is traversed from a hypothesis back to the facts that support the hypothesis.Keywords: Expert System, Artificial Intelligence, Certainty Factor, Website